CpG Oligodeoxynucleotides Enhance the Efficacy of Adoptive Cell Transfer Using Tumor Infiltrating Lymphocytes by Modifying the Th1 Polarization and Local Infiltration of Th17 Cells. (29th September 2010) - Xu, Lin; Wang, Chunhong; Wen, Zhenke; Zhou, Ya; Liu, Zhongmin; Liang, Yongjie; Xu, Zengguang; Ren, Tao
Abstract : Adoptive cell transfer immunotherapy using tumor infiltrating lymphocytes (TILs) was an important therapeutic strategy against tumors. But the efficacy remains limited and development of new strategies is urgent. Recent evidence suggested that CpG-ODNs might be a potent candidate for tumor immunotherapy. Here we firstly reported that CpG-ODNs could significantly enhance the antitumor efficacy of adoptively transferred TILs in vivo accompanied by enhanced activity capacity and proliferation ofCD 8 + T cells andCD 8 + T cells, as well as a Th1 polarization immune response. Most importantly, we found that CpG-ODNs could significantly elevate the infiltration of Th17 cells in tumor mass, which contributed to anti-tumor efficacy of TILs in vivo. Our findings suggested that CpG ODNs could enhance the anti-tumor efficacy of adoptively transferred TILs through modifying Th1 polarization and local infiltration of Th17 cells, which might provide a clue for developing a new strategy for ACT based on TILs.